2010
DOI: 10.1021/np100030x
|View full text |Cite
|
Sign up to set email alerts
|

Eremophilane-Type Sesquiterpenes from the Fungus Xylaria sp. BCC 21097

Abstract: Seven new eremophilane-type sesquiterpenoids (1-5, 7, and 8) and the known mairetolide F (6) were isolated from the endophytic Xylaria sp. BCC 21097. A new furofurandione (9) was also isolated from the fungal extract. The structures of the new compounds were elucidated by analyses of NMR spectroscopic and mass spectrometry data in combination with chemical reaction studies. Eremophilanolides possessing an alpha-methylene-gamma-lactone (1-3) exhibited moderate cytotoxic activities, while related analogues beari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 22 publications
(60 reference statements)
3
44
0
Order By: Relevance
“…C. lusitanica [78] Mairetolide F Xylaria sp. L. spinosa [76] Valencene M. albus C. zeylanicum [45] unidentified vine plant [79] Oryza granulata [62] Xylaria sp. C. lusitanica [78] Eudesmanes, eudesmenes (selinenes)…”
Section: Phytohormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…C. lusitanica [78] Mairetolide F Xylaria sp. L. spinosa [76] Valencene M. albus C. zeylanicum [45] unidentified vine plant [79] Oryza granulata [62] Xylaria sp. C. lusitanica [78] Eudesmanes, eudesmenes (selinenes)…”
Section: Phytohormonesmentioning
confidence: 99%
“…[91] unnamed compounds Xylaria sp. Licuala spinosa [76] Xylaria sp. mangrove plant [92] Xylarenones Xylaria sp.…”
Section: Albusmentioning
confidence: 99%
“…Previous investigations have revealed that fungi of the genus Xylaria are a rich source of structurally diverse natural products. Examples include the HIV-1 integrase inhibitor integric acid [1], the cytotoxic agents xyloallenolide A [2] and eremophilanolides [3], the antifungal metabolites multiplolides A and B [4], the acetylcholinesterase inhibitors xyloketals [5], the NPY Y5 receptor antagonists xylarenals A and B [6], the chemokine receptor antagonist 19,20-epoxycytochalasin Q [7], the anti-herpes simplex virus agent mellisol [8].…”
mentioning
confidence: 99%
“…BCC 21097 associated with Licuala spinosa. The three compounds, eremophilanolide 62, 63, and 64 exhibited moderate cytotoxic activity with IC 50 values of 3.8-21 µM against cancer cell lines KB, MCF-7, and NCI-H187 (Isaka et al 2010).…”
Section: Compounds From Endophytic Fungi Of Terrestrial Plantsmentioning
confidence: 99%